The representation of the public square in the works of Bruegel: A perspective from cultural theory - Özpek, Handan Şule (My University, 2018)
Artworks offer more than aesthetic scenes. Once they are examined critically, these compositions may offer diverse experience and knowledge. Their contribution to socio-historical progression may be more than they are perceived. This thesis attempts to illuminate the essence and the key factors of some of the artworks of the great Netherlandish artist Pieter Bruegel. He utilized his brush to present the social interactions of 16th century Europe. His remarkable ability of observation contributed to historiography by conveying sociological and historical events literally. Bruegel preferred to illustrate scenes from life with all their reality and vulgar details, rather than portraying pleasant themes, only. His depictions of ordinary people in their natural appearances provided him with a unique place among the Renaissance painters. He was significantly successful in depicting the codes of traditional practices of the society of his time. Bruegel lived in Antwerp. This city was located at an important geopolitical point and therefore, he encountered a lot of people from different languages and cultures. These influences prepared the ground for him to blend scenes from the social life and scenes from the Bible. In this dissertation, artworks of Bruegel are discussed within the framework of the historical structure of the period in which he lived and the concept of art during Renaissance. Through this macro perspective, the aim is to make the social facts more understandable. In particular, his depictions of town squares is examined in detail. These items can be perceived as a mirror that reflects everyday life of ordinary people in the 16th century; thus, they can contribute to historiography.

Sanat eserleri estetik görünümden daha fazlasını sunar. Eleştirel şekilde incelenmeleri halinde bu kompozisyonlar çeşitli bilgi ve deneyimleri edinmemizi sağlayabilir. Böylece, sanat eserlerinin sosyo-tarihsel ilerlemeye katkısı, görsel olarak algılandığından fazla olabilir. Bu tez, Hollandalı büyük sanatçı Pieter Bruegel’ in bazı sanat eserlerinin özünü ve temel faktörlerini aydınlatmayı amaçlamaktadır. Bruegel fırçasını 16. yüzyılda Avrupa’daki sosyal etkileşimleri yansıtmak için kullanmıştır. Gözlem yeteneğini kullanarak sosyolojik ve tarihsel olayları gerçeğe uygun şekilde aktarmış ve tarih yazıcılığına katkıda bulunmuştur. Bruegel, yalnızca hoş temalı eserler üretmek yerine gerçek hayatta karşılaştığı olayları tüm gerçeklikleri ve hatta kaba ayrıntıları ile aktarmayı tercih etmiştir. Sıradan insanları doğal hallerinde resmetmesi onun Rönesans ressamları arasında eşsiz bir yere sahip olmasını sağlamıştır. Bu yaklaşımıyla Bruegel, içinde yaşadığı toplumun geleneklerini betimlemede önemli ölçüde başarılı olmuştur. Bruegel’in Antwerp’te yaşamış olması, farklı dil ve kültürden çok sayıda insanla karşılaşmasını sağlamıştır. Tüm bu etkiler, sosyal yaşamdan aldığı esin ile İncil’de geçen bazı bölümleri harmanlayarak resmetmesi için Bruegel’ e zemin hazırlamıştır. Bu tez çalışmasında, Bruegel’in eserleri, içinde yaşadığı dönemin tarihsel yapısı ve Rönesans döneminin sanat anlayışı çerçevesinde incelenmiştir. Bu makro bakış açısıyla, eserlerdeki sosyal olguların daha anlaşılır hale getirilmesi amaçlanmaktadır. Özellikle, birçok sosyal unsura ev sahipliği yapan kasaba meydanlarının betimlemeleri incelenmiştir. Bu unsurlar, 16. yüzyılda sıradan insanların gündelik hayatlarını yansıtan bir ayna olarak algılanabilir ve böylece tarih yazıcılığına katkıda bulunabilirler.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Pieter Bruegel; Bruegel'in resimlerine sosyolojik bakış açısı; Sociological aspects in Bruegel's paintings